Digital anthropology
1 online resource (xii, 336 pages)
Keywords: "Digital Anthropology 2nd Edition explores how human and digital can be defined in relation to one another within issues as diverse as social media use, virtual worlds, hacking, quantified self, blockchain, digital environmentalism and digital representation. The book challenges the moral universal of the digital by exploring emergent anxieties about the global spread of new technological forms as well as highlighting the productive contribution of the digital to new concepts and practices. In this fully revised edition, Digital Anthropology reveals how the intense scrutiny of ethnography can overturn assumptions about the impact of digital culture and reveal its profound consequences for everyday life around the world. Combining the clarity of case studies with an engaging style that conveys a passion for new frontiers of enquiry within anthropological study, this will be essential reading for students and scholars interested in theory of anthropology, media and information studies, communication studies and sociology. With a brand new introduction from editors Haidy Geismar and Hannah Knox, as well as the original introduction by Heather Horst and Daniel Miller, in conjunction with new chapters on hacking, and digitizing environments, amongst others, and fully revised chapters throughout, this will bring the field-defining overview of digital anthropology fully up to date"--